British imperialism and Turkish nationalism - Xypolia, Ilia, author.
1 online resource.
Keywords: As Cyprus experienced British imperial rule between 1878 and 1960, Greek and Turkish nationalism on the island developed at different times and at different speeds. Relations between Turkish Cypriots and the British on the one hand, and Greek Cypriots and the British on the other, were often asymmetrical with the Muslim community undergoing an enormous change in terms of national/ethnic identity and class characteristics. Turkish Cypriot nationalism developed belatedly as a militant nationalist and anti-Enosis movement. This book explores the relationship between the emergence of Turkish national identity and British colonial rule in the 1920s and 1930s.